Identification and Outcomes of Hospitalized Medically Ill Patients Who Are Candidates for Extended Duration Thromboprophylaxis - Coleman, Craig I.; Piazza, Gregory; Ashton, Veronica; Bunz, Thomas J.; Spyropoulos, Alex C. (TH Open, 2020)
Background Extended duration thromboprophylaxis (ET) for approximately 30 days can effectively and safely reduce venous thromboembolism (VTE) risk in appropriately selected medically ill patients. We sought to estimate the proportion of hospitalized medically ill patients potentially qualifying for ET and assess their post-discharge clinical and economic outcomes using a large claims database.Methods Using MarketScan claims from January 2012 to September 2018, we identified medically ill patients hospitalized with a primary diagnosis of heart failure, respiratory insufficiency, ischemic stroke, infection, or inflammatory disease and ≥1-additional risk factor for VTE. Patients < 40 years old, a length-of-stay < 3 or >30 days, receiving oral anticoagulation prior to index hospitalization or having an indication for full-dose anticoagulation were excluded, as were patients deemed high-risk for bleeding due to active, in-hospital treated cancer, gastroduodenal ulcer or bleeding within the prior 3 months, bronchiectasis, pulmonary cavitation or hemorrhage, or dual antiplatelet therapy use.Results We identified 2,782,988 patients ≥40 years of age and admitted for a high-risk medical illness. Of these, 724,531 patients (26.0%) were identified as ET candidates. Patients' VTE risk appeared highest in the first 30 days post-discharge (1,532/724,531, 0.2%). Adjusted post-index hospitalization costs (2018 US$) for patients with a VTE within 30 days were higher than those without VTE (Δ = $32,623 at 30 days, Δ = $43,325 at 90 days, Δ = $53,668 at 365 days; p < 0.001 for all).Conclusion Post-discharge VTE in high-risk patients with medical illness is associated with substantially increased costs.
Keywords: anticoagulation; extended duration thromboprophylaxis; medically ill; venous thromboembolism; prevention